The effects of social pensions on mortality among the extreme poor elderly - Valderrama Torres, José Artemio (2023)
We studied the effects that Peru’s social pension programme, Pensión 65, had on mortality. The programme provides pensions to people aged 65 and older who do not have other pension benefits and are extreme poor. The analysis relies on survey data obtained at the baseline and matched to mortality records of 2012-2019. We exploited the discontinuity around the welfare index used by the programme to determine eligibility, and estimate intention-to-treat effects. We found that, after seven years, the programme could reduce mortality among eligible people by about 11.4 percentage points, implying an increase in life expectancy of about one year.